Matriglycan: a novel polysaccharide that links dystroglycan to the basement membrane - Yoshida-Moriguchi, Takako (Glycobiology, 2015)
Associations between cells and the basement membrane are critical for a variety of biological events including cell proliferation, cell migration, cell differentiation and the maintenance of tissue integrity. Dystroglycan is a highly glycosylated basement membrane receptor, and is involved in physiological processes that maintain integrity of the skeletal muscle, as well as development and function of the central nervous system. Aberrant O-glycosylation of the α subunit of this protein, and a concomitant loss of dystroglycan's ability to function as a receptor for extracellular matrix (ECM) ligands that bear laminin globular (LG) domains, occurs in several congenital/limb-girdle muscular dystrophies (also referred to as dystroglycanopathies). Recent genetic studies revealed that mutations in DAG1 (which encodes dystroglycan) and at least 17 other genes disrupt the ECM receptor function of dystroglycan and cause disease. Here, we summarize recent advances in our understanding of the enzymatic functions of two of these disease genes: the like-glycosyltransferase (LARGE) and protein O-mannose kinase (POMK, previously referred to as SGK196). In addition, we discuss the structure of the glycan that directly binds the ECM ligands and the mechanisms by which this functional motif is linked to dystroglycan. In light of the fact that dystroglycan functions as a matrix receptor and the polysaccharide synthesized by LARGE is the binding motif for matrix proteins, we propose to name this novel polysaccharide structure matriglycan.